Creating the “Romusha” Identity Among Day Laborers: A Focus on the Mini-Magazine “Romusha Tosei” (1974-1985) - NAKAYAMA, Hiroaki (THE JAPANESE JOURNAL OF EDUCATIONAL RESEARCH, 2024)
This study aims to reveal the creation of the “Romusha” identity through the cultural movement that originated from the magazine “Romusha Tosei” (1974-1985), published in Kamagasaki. While abundant discussions about social exclusion and inclusion in pedagogy exist, one issue pointed out has been the overlooking of the autonomy of the persons involved. Thus, recent years have seen increased discussion of an approach that focuses on the practice and actions of the persons themselves. Elsewhere, this study focuses on the resistance to exclusion in more localized life areas, preceding the practice and actions of the persons themselves. In particular, it is necessary to examine how collective identity formation in individual lives serves as the foundation for resistance. The subject of this study is Kamagasaki, an area designated for day laborers (yoseba), which faces the problem of social exclusion. It is also an area where a multilayered safety net for resisting exclusion has been formed. This study explores the identity formation of day laborers, focusing on the cultural movement that originated from the magazine “Romusha Tosei,” which indirectly influenced the formation of the safety net. The researcher analyzed “Romusha Tosei” and related historical materials, as well as conducting interviews with a writer involved with the magazine. Consequently, this study revealed the unique process in which the identity of day laborers was explored and created through “Romusha Tosei.” There were two main orientations therein. One was an exploration of the “history of day laborers,” who became subjects with historicity. The other was an exploration of the “life culture of day laborers.” Their sense of camaraderie and solidarity was expressed through their life experiences. In addition, the boundaries of their identity were an issue. Power dynamics in the lower working class underwent complicated intersections. Day laborers developed a unique identity as employed persons to overcome this difficult circumstance. These findings suggest that it is possible to discover an alternative concept of inclusion based on the agency of the individuals targeted for inclusion. There are two key points to highlight: one is the proposition of an inclusive image that allows for mutual recognition among stakeholders without the provision of competence by the majority society, while the other is the proposal of an approach that creates communities driven by the agency of stakeholders on the social periphery.